Factors associated with dengue fever outbreak in Dire Dawa administration city, October, 2015, Ethiopia - case control study - Luna Habtamu Degife; Yoseph Worku; Desalegn Belay; Abyot Bekele; Zegeye Hailemariam (BMC, 2019)
Abstract Background Dengue Fever (DF) is underrecognized mosquito borne viral disease prevalent in tropical and subtropical regions. In 2013, Ethiopia reported the first confirmed DF outbreak in Dire Dawa city which affected 11,409 people. During the outbreak investigation, we determined factors associated with DF and implemented control measures. Methods We conducted a 1:2 un-matched case control study from October 7-15/2015. Case was any person with fever of 2-7 days and more than two symptoms: headache, arthralgia, myalgia, rash, or bleeding from any part of the body. We recruited participants using purposive sampling from health facilities and used structured questionnaire to collect data. Multiple logistic regression analysis was conducted to control confounders and to identify factors associated with DF. Sixty-nine serum-samples were tested by Enzyme-Linked Immunosorbent Assay (ELISA). Results We enrolled 210 participants (70 cases and 140 controls) in the study. Females accounted for 51.4% of cases and 57.1% of controls. The mean age was 23.7 ± 9.5 standard deviation (SD) for cases and 31.2 ± 13 SD for controls. Close contact with DF patient (Adjusted odds ratio [AOR] =5.36, 95% confidence interval [CI]: 2.75-10.44), nonuse of bed-nets (AOR = 2.74, 95% CI: 1.06-7.08) and stagnant water around the village (AOR = 3.61, 95% CI: 1.31-9.93) were independent risk factors. From the samples tested, 42 were confirmed positive. Conclusions Individuals who live with DF patient, around stagnant water and do not use bed nets are at high risk of contracting the disease. Health education on DF prevention was given and mosquito breeding sites were drained. Strong vector prevention strategies are recommended by enhancing the existing malaria prevention and control program.